Creative Musical Work "Galuik Balam" in the Aesthetic Context of Minangkabau Traditional Music - Rafiloza, Rafiloza; Rasmida, Rasmida; Marh, Fahmi; Munafri, Sastra; Minawati, Rosta; Batubara, Junita (Research Journal in Advanced Humanities, 2025)
This research aimed to develop a model for creating intertextual musical art by combining compositions related to Minangkabau songs Anak Balam and Balam-balam, thereby offering creative alternatives for musical elements in Minangkabau social events. The methodology involves concept development and realization, including exploring the essence of Balam-balam and Anak Balam, creating musical dialogue, selecting appropriate instruments, constructing music based on the mystical atmosphere of Anak Balam, integrating traditional and non-traditional instruments, incorporating dramatic elements, structuring the work into three parts, weaving themes, balancing timbre, and titling each section. The results indicated that the Balam-balam and Anak Balam phenomena form three interrelated parts: Romance, Loyalty, and Sacred, each with subsections. The Romance section has four subsections, while both the Loyalty and Sacred sections have one each. This musical work portrayed harmony and affection using diverse traditional, modern, and non-musical instruments, and alternating vocals. The work Galuik Balam demonstrates that blending traditional Minangkabau musical elements with natural bird sounds and new musical forms enhances the understanding of Minangkabau cultural aesthetics and significantly contributes to the development of traditional musical arts in Indonesia.